(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
A parchment fragment discovered in 2009 in the Archive of the Basilica of San Petronio in Bologna is a bifolium today kept in the folder 716/1, 1 (olim folder 353, envelope 3). The scriptio superior contains some passages from St Augustine’s De civitate Dei, while the scriptio inferior is a text in Gothic writing and language containing passages from Wulfila’s translations of the Bible. We were the first to transcribe the Gothic text of the parchment bifolium and to translate it into Italian. The linguistic analysis enabled us to cast new light on some traits in the use of pre-verbs, conjunctions, synonyms, word-formation, loan-translations, new words alongside rare ones as well as new compounds, enriching that way the Gothic vocabulary. The aim of this paper is to provide a follow-up examination of the Gothic Bologna palimpsest. KEYWORDS: Latin, Gothic, palimpsest, translation, lexicon